Tinjauan Desain Kemasan Boxset Musik Sebagai Strategi Penjualan Rilisan Fisik Di Yogyakarta - Arsita Pinandita (AKSA: Jurnal Desain Komunikasi Visual, 2019)
The Design of music album packaging in Indonesia especially Yogyakarta still fairly rare. In the midst of lethargy for physical release purchasing by music lovers. This paper would refers to: Kind of content(s) will be a visual image in the design of boxset packaging to be having a strong character. Above formulation has purpose to intend understanding ( the working role) or collaboration between graphic designers and musicians for releasing of boxset format music albums, also to identify the commodification of popular culture, making music boxset as part of the commodity of music collectors. The existence of music boxset should not be separated from the collaboration between graphic designers and musicians, because a music boxset will be in demand in the market if it is visually able to combine the collaboration to be able to invite consumer interest. Music album designers are also required to be able to innovate to the development of the media, so that music boxset can be accepted by music lovers and innovative music industry that is evolving in the digital domain.